FV 6. Factors influencing the adequacy of determining hemispheric language lateralization in presurgical epilepsy patients using functional transcranial Doppler sonography (fTCD). Issue 8 (August 2021) - Conradi, N.; Salim, M.; Behrens, M.; Hermsen, A.; Kannemann, T.; Merkel, N.; Schuster, A.M.; Strzelczyk, A.; Rosenow, F.
Abstract : Introduction . Functional transcranial Doppler sonography (fTCD) has become part of the routine work-up of epilepsy patients considered as candidates for epilepsy surgery in many epilepsy centers [1]. The adequacy of determining hemispheric language lateralization (HLL) using fTCD is of special importance, given its contribution to the prediction of possible postsurgical cognitive risks, and thus the planning of epilepsy surgery. Therefore, this study aimed to identify predictive factors for receiving inconclusive HLL results using fTCD. Methods . Data from 266 epilepsy patients who received fTCD to determine HLL before epilepsy surgery between 2015 and 2020 was analyzed retrospectively. A phonemic word generation paradigm was used, and fTCD was performed in a standardized fashion as described previously [2]. Logistic regression analyses were conducted to model the odds of receiving inconclusive HLL results based on several potential predictor variables. Results . Hemispheric language lateralization was left-sided in 147 patients (55.2%), right-sided in 43 patients (16.2%), and inconclusive in 76 patients (28.6%). Univariate logistic regression analyses revealed significant associations between a reduced probability of inconclusive HLL results and higher age, female gender, right-handedness, German native language, more years of education, older age at onset of epilepsy, temporal localization of the epileptogenic focus, etiology of hippocampal sclerosis, higher verbal IQ, and higher semantic and phonemic verbal fluency. In a multivariate model (overall percentage accuracy in classification = 71.5%, p < 0.001), only years of education (adjusted OR = 0.91, p < 0.001) remained independently predictive for a reduced probability of inconclusive HLL results. Discussion. Our findings indicate that the adequacy of determining HLL in presurgical epilepsy patients using fTCD is highly dependent on the patients" education. On this basis, we recommend not to use the same paradigm for all patients, but to individually adapt the complexity of the task to the cognitive abilities of each patient. Therefore, the development and standardization of additional word generation paradigms for fTCD (e.g. based on semantic cues, or picture description) is encouraged, to further facilitate an appropriate presurgical evaluation of every epilepsy surgery candidate. References [1] Vogt, V. et al. (2017). Current standards of neuropsychological assessment in epilepsy surgery centers across Europe. Epilepsia, 58 (3), 343-355. [2] Conradi, N. et al. (2019). Hemispheric language lateralization in presurgical patients with temporal lobe epilepsy: Improving the retest reliability of functional transcranial Doppler sonography. Epilepsy & Behavior, 91, 48-52.